Structure, organization, and expression of the alpha prolamin multigenic family bring new insights into the evolutionary relationships among grasses - Correa de Souza, Rafael Soares; Balbuena, Tiago Santana [UNESP]; Arruda, Paulo (Crop Science Soc Amer, 2015)
Prolamins are the major seed storage proteins of grasses. In maize and related species, prolamins are classified into alpha-, beta-, gamma-, and delta-subclasses by their solubility properties. alpha-prolamins are encoded by multigene families and have a secondary structure that consists of tandem alpha-helix repeats. Maize has two alpha-prolamin subclasses, namely the 19 and 22 kDa subclasses that contain nine and 10 alpha-helix repeats, respectively. Here, we present an evolutionary study based on the structure, organization, and expression of alpha-prolamins in maize, sugarcane, sorghum, and coix. True 22 kDa subclasses containing 10 repeats are conserved in all four species, but true 19 kDa subclasses containing nine repeats are found only in maize and sugarcane. We discovered a 19 kD alpha-like a-coixin that, as in sorghum, is encoded by few genes. These data suggest that a 19 kDa progenitor present in the ancestor common to maize, coix, sorghum, and sugarcane was preserved at low copy number in coix and sorghum, while amplified into multigene family architecture in maize and sugarcane. The expression profiling of alpha-prolamins, verified by two-dimensional gels, showed highly conserved multispot composition for the 19 kDa alpha-prolamins in maize and sugarcane. Coix and sorghum did not present true 19 kDa alpha-prolamin spots. Our data show remarkable similarity between maize and sugarcane 19 kDa alpha-prolamins regarding both gene structure and expression. Since the multigene architecture of 19 kDa alpha-canein appeared after sugarcane diverged from sorghum, our data suggest that maize and sugarcane might have acquired the multigene family encoding these storage proteins from a common ancestor.